A permanent magnet surface coating material and preparation method

By using a combination of styrene-propylene resin composite liquid, alloy composite powder, molybdenum oxide powder and silicon carbide powder, a permanent magnet surface coating with high corrosion resistance and adhesion is formed, and the problem of oxidation and corrosion of neodymium iron boron magnets is solved. Its corrosion resistance and industrial production applicability have been significantly improved.

CN116731567BActive Publication Date: 2024-12-17XUZHOU NANFANG YONGCI MATERIAL
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310791867.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2024-12-17
Estimated Expiration
2043-06-30

AI Technical Summary

Technical Problem

Neodymium iron boron magnets are prone to oxidation and corrosion, resulting in insufficient corrosion resistance, limiting their application range. The corrosion resistance of the prior art needs to be further improved.

Method used

The combination of styrene-propylene resin composite liquid, alloy composite powder, molybdenum oxide powder and silicon carbide powder is used to form the permanent magnet surface coating material evenly through stirring. The alloy composite powder is composed of zinc-based alloy powder and iron-chromium alloy powder, and rare earth elements are added. To improve strength and corrosion resistance, molybdenum dioxide and silicon carbide powder enhance adhesion and thermal conductivity.

Benefits of technology

It significantly improves the corrosion resistance and adhesion of the permanent magnet surface coating material, extends its service life in high temperature and high pressure environments, and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004313848140000011
    Figure HDA0004313848140000011
Patent Text Reader

Abstract

The invention discloses a permanent magnet surface coating material and a preparation method thereof, the preparation method comprising: mixing styrene-acrylic resin, melamine formaldehyde resin, chromium oxide and methanol to form a styrene-acrylic resin composite liquid; then mixing alloy composite powder, molybdenum dioxide powder and silicon carbide powder, and then slowly adding the styrene-acrylic resin composite liquid and stirring to obtain a permanent magnet surface coating material, wherein the alloy composite powder is composed of zinc-based alloy powder and iron-chromium alloy powder. The permanent magnet surface coating material prepared by the invention has both high strength and high corrosion resistance, and the preparation method has a simple process, low production cost and is suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of corrosion-resistant coating preparation technology, and in particular to a permanent magnet surface coating material and a preparation method thereof. Background Art

[0002] A magnet that can maintain its magnetism for a long time is called a permanent magnet. Such as natural magnetite (magnetite) and artificial magnet (aluminum nickel cobalt alloy). Permanent magnets are also called hard magnets, which are not easy to lose magnetism or magnetization. Permanent magnets have a wide range of applications, including televisions, speakers, audio speakers, radios, bag buckles, data cable magnetic rings, computer hard drives, mobile phone vibrators, etc. Neodymium iron boron magnets, also known as powerful magnets or magnetic kings, are the highest performance permanent magnets in the current commercial market. They have strong magnetic properties, high machinability, hard texture, and high cost performance. Therefore, they are extremely widely used. However, they have the disadvantages of unstable properties and easy oxidation and corrosion, which limits their application. Therefore, it is very important to prepare a permanent magnet surface coating material with strong corrosion resistance.

[0003] The invention patent with application number CN201810438127.X discloses a method for preparing a high corrosion-resistant coating on the surface of a sintered NdFeB magnet. The processed NdFeB magnet is pretreated and soaked in a pretreatment solution prepared by mixing distilled water, a coating agent and an accelerator. The ZnAl coating liquid is applied to the surface of the NdFeB magnet after soaking to obtain a NdFeB magnet with a ZnAl coating. Finally, the Al-rich coating liquid is applied to the surface of the NdFeB magnet after the primer to obtain a highly corrosion-resistant NdFeB magnet. Through two spraying processes, the porosity between the magnet and the corrosive medium is effectively reduced, the bonding force between the coating and the magnet is improved, and the sintered NdFeB magnet has good corrosion resistance. The ZnAl coating of the primer greatly reduces the medium that enters the deeper layer of the coating, thereby greatly improving the magnet's resistance to high temperature, high pressure and aging. However, the corrosion resistance needs to be improved.

[0004] Therefore, the present invention provides a permanent magnet surface coating material and a preparation method thereof. The prepared surface coating material has high corrosion resistance, simple process, low production cost, and is suitable for industrial production. Summary of the invention

[0005] The first object of the present invention is to provide a method for preparing a permanent magnet surface coating material in view of the deficiencies in the prior art. The method has a simple process, low production cost and is suitable for industrial production.

[0006] The second object of the present invention is to provide a permanent magnet surface coating material having both high strength and high corrosion resistance.

[0007] The present invention adopts the following technical solutions:

[0008] (1) A method for preparing a permanent magnet surface coating material, comprising the following steps:

[0009] S1, mixing styrene-acrylic resin, melamine formaldehyde resin, chromium oxide and methanol to form a styrene-acrylic resin composite liquid;

[0010] S2, mixing and stirring the alloy composite powder, molybdenum dioxide powder and silicon carbide powder, and then slowly adding the styrene acrylic resin composite liquid prepared in S1, stirring, to obtain a permanent magnet surface coating material, wherein the alloy composite powder is composed of zinc-based alloy powder and iron-chromium alloy powder.

[0011] Furthermore, in S1, the weight ratio of styrene acrylic resin, melamine formaldehyde resin, chromium oxide and methanol is 1:0.2-0.4:0.05:0.6-0.9.

[0012] Furthermore, in S2, the weight percentage contents of alloy composite powder, molybdenum dioxide powder and silicon carbide powder are 35-45%, 3-6% and 3-6% respectively, and the rest is styrene-acrylic resin composite liquid.

[0013] Furthermore, in S2, in the alloy composite powder, the weight ratio of the zinc-based alloy powder to the iron-chromium alloy powder is 1:0.4-0.7.

[0014] Furthermore, in S2, the composition and weight percentage of the zinc-based alloy powder are: Al is 25.0-28.0%, Mg is 0.01-0.02%, Cu is 2-2.5%, Sn is 0.15-0.25%, Pb is 0.01%-0.04%, Y is 0.1%-0.4%, Ce is 0.5%-0.7%, and the rest is Zn.

[0015] Furthermore, the preparation method of the zinc-based alloy powder is as follows: take the waste of ZnAl27 alloy, put it into an induction furnace, add rare earth elements Sn, Pb, Y and Ce, melt them together, and then cast them into alloy ingots; put the alloy ingots into the crucible of the induction furnace for melting, the crucible is provided with a bottom hole with a diameter of 1 to 2 mm, and after the alloy is melted, it flows out from the bottom hole under the action of nitrogen pressure, and contacts with the molybdenum alloy wheel rotating below the bottom hole of the crucible to form alloy strips; then put the alloy strips into a ball mill for crushing to form zinc-based alloy powder.

[0016] Furthermore, the temperature at which the scrap ZnAl27 alloy, Sn, Pb, Y and Ce are melted together is 690-750°C; the melting temperature of the alloy ingot is 720-750°C, and the alloy is kept warm for 5-9 minutes after melting; the nitrogen pressure is 1.1-1.3 atmospheres, and the linear speed of the edge of the molybdenum alloy wheel is 19-23 m / s; the ball milling temperature is -30--50°C, and the particle size of the zinc-based alloy powder after ball milling is 220-250 mesh.

[0017] Furthermore, in S2, the composition and weight percentage of the ferrochromium alloy powder are: C is 0.03-0.08%, Si is ≤1%, Mn is ≤2%, Cr is 18-20%, Ni is 8-11%, Zr is 0.05-0.12%, Gd is 0.1-0.4%, Pd is 0.5-0.7%, P is ≤0.05%, S is ≤0.03%, and the rest is Fe.

[0018] Furthermore, the preparation method of the ferrochromium alloy powder is as follows: take 304 stainless steel waste, put it into an induction furnace, add rare earth elements Zr, Gd and Pd, melt them together, and then cast them into alloy ingots; put the alloy ingot into the crucible of the induction furnace for melting, the crucible is provided with a bottom hole with a diameter of 1 to 2 mm, and after the alloy is melted, it flows out from the bottom hole under the action of nitrogen pressure and contacts with the molybdenum alloy wheel rotating below the bottom hole of the crucible to form alloy strips; then put the alloy strips into a ball mill for crushing to form ferrochromium alloy powder.

[0019] Furthermore, the temperature at which 304 stainless steel scrap, Zr, Gd and Pd are melted together is 1500-1560°C; the melting temperature of the alloy ingot is 1530-1580°C, and the alloy is kept warm for 5-10 minutes after melting; the nitrogen pressure is 1.1-1.3 atmospheres, and the linear speed of the edge of the molybdenum alloy wheel is 18-24 m / s; the particle size of the iron-chromium alloy powder after ball milling is 200-250 mesh.

[0020] Furthermore, in S2, the mixing stirring time of the alloy composite powder, molybdenum dioxide powder and silicon carbide powder is 20 to 25 minutes, and the stirring speed is 40 to 50 rpm; after adding the styrene acrylic resin composite liquid, the stirring time is 20 to 30 minutes, and the stirring speed is 900 to 1000 rpm; the particle size of the alloy composite powder, molybdenum dioxide powder and silicon carbide powder is 200-280 mesh.

[0021] (ii) The present invention also provides a permanent magnet surface coating material prepared by the above-mentioned preparation method, which has high corrosion resistance.

[0022] Beneficial effects:

[0023] (1) A part of the alloy powder in the present invention is an iron-chromium alloy powder, which is made of stainless steel scrap and rare earth elements Zr, Gd and Pd. The Cr and Ni content is high and the corrosion resistance is very good. The addition of Zr, Gd and Pd refines the grains of the steel and improves the strength of the alloy powder itself.

[0024] (2) Another part of the alloy powder in the present invention is zinc-based alloy powder, which is made of waste zinc alloy and rare earth elements Sn, Pb, Y and Ce. Similarly, the addition of Y and Ce refines the grains; the addition of Sn and Pb plays a role in solid solution strengthening, which improves the strength of the alloy powder itself; the presence of Al and Zn in large quantities ensures the corrosion resistance of the coating;

[0025] (3) In the present invention, the iron-chromium alloy powder and the zinc-based alloy powder exist at the same time. The Al and Zn in the zinc-based alloy not only protect the steel substrate, but also protect the iron-chromium alloy powder in the coating, thereby ensuring that the skeleton of the coating does not fall apart in a corrosive environment; in addition, since molybdenum dioxide and silicon carbide are very stable, the presence of molybdenum dioxide and silicon carbide further ensures the integrity of the coating, thereby ensuring that the coating has sufficient adhesion;

[0026] (4) In the present invention, the resin composite liquid has good compatibility with the alloy composite powder, molybdenum dioxide powder, and silicon carbide powder, and can organically combine the alloy composite powder, molybdenum dioxide powder, and silicon carbide powder with the steel, thereby ensuring the adhesion of the coating to the magnet substrate;

[0027] (5) In the present invention, since silicon carbide has high hardness and wear resistance, the silicon carbide powder as a component of the coating increases the wear resistance of the coating and protects the alloy powder; molybdenum dioxide and silicon carbide have good thermal conductivity, thereby improving the heat dissipation function of the coating, which are all conducive to improving the adhesion. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a surface morphology of the permanent magnet surface coating prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution of the present invention will be clearly and completely described in combination with the embodiments below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0030] The experimental methods used in the following examples are conventional methods unless otherwise specified, and the reagents, methods and equipment used are conventional reagents, methods and equipment in the art unless otherwise specified.

[0031] Example 1

[0032] This embodiment provides a method for preparing a permanent magnet surface coating material.

[0033] (1) Preparation of styrene-acrylic resin composite liquid:

[0034] Styrene acrylic resin, melamine formaldehyde resin, chromium oxide and methanol were weighed respectively according to a weight ratio of 1:0.2:0.05:0.6, and mixed and stirred evenly to form a styrene acrylic resin composite liquid.

[0035] (2) Preparation of zinc-based alloy powder:

[0036] Take the scrap of ZnAl27 alloy, put it into an induction furnace, add rare earth elements Sn, Pb, Y and Ce, melt them together at 690℃, and then cast them into alloy ingots;

[0037] The alloy ingot is placed in an induction furnace crucible for melting at a melting temperature of 720° C. After melting, the alloy ingot is kept warm for 5 minutes. The crucible is provided with a bottom hole with a diameter of 1 mm. After melting, the alloy ingot flows out from the bottom hole under the action of nitrogen pressure (1.1 atmospheres) and contacts the molybdenum alloy wheel rotating below the bottom hole of the crucible (the linear speed of the edge of the molybdenum alloy wheel is 20 m / s) to form an alloy strip; then the alloy strip is placed in a ball mill at -30° C. and crushed to form a zinc-based alloy powder with a particle size of 220 meshes;

[0038] The components and weight percentages of the prepared zinc-based alloy powder are as follows: Al is 26.0%, Mg is 0.02%, Cu is 2.5%, Sn is 0.15%, Pb is 0.03%, Y is 0.2%, Ce is 0.5%, and the rest is Zn.

[0039] (3) Preparation of ferrochromium alloy powder:

[0040] Take 304 stainless steel scrap, put it into an induction furnace, add rare earth elements Zr, Gd and Pd, melt them together at 1500℃, and then cast them into alloy ingots;

[0041] The alloy ingot is placed in an induction furnace crucible for melting at a melting temperature of 1530° C. After melting, the alloy is kept warm for 10 minutes. The crucible is provided with a bottom hole with a diameter of 1 mm. After the alloy is melted, it flows out from the bottom hole under the action of nitrogen pressure (1.1 atmospheres) and contacts the molybdenum alloy wheel rotating below the bottom hole of the crucible (the linear speed of the edge of the molybdenum alloy wheel is 20 m / s) to form an alloy strip; then the alloy strip is placed in a ball mill and crushed to form an iron-chromium alloy powder with a particle size of 220 meshes;

[0042] The components and weight percentages of the prepared ferrochromium alloy powder are as follows: C is 0.05%, Si is 1%, Mn is 1%, Cr is 18%, Ni is 11%, Zr is 0.10%, Gd is 0.4%, Pd is 0.5%, P is 0.03%, S is 0.03%, and the rest is Fe.

[0043] (4) Preparation of permanent magnet surface coating material:

[0044] The zinc-based alloy powder and the iron-chromium alloy powder are uniformly mixed in a weight ratio of 1:0.4 to form an alloy composite powder;

[0045] The alloy composite powder, molybdenum dioxide powder and silicon carbide powder are mixed and stirred for 20 minutes at 40 revolutions per minute, and then the styrene-acrylic resin composite liquid prepared in step (1) is slowly added and stirred for 20 minutes at 1000 revolutions per minute to obtain a permanent magnet surface coating material. The weight percentages of the alloy composite powder, molybdenum dioxide powder and silicon carbide powder are 35%, 3% and 3% respectively, and the rest is the styrene-acrylic resin composite liquid.

[0046] (5) Application:

[0047] The permanent magnet surface coating material prepared in this embodiment is applied to the surface coating of a NdFeB magnet, and the corrosion resistance of the formed coating is tested.

[0048] After testing, the permanent magnet composite material was placed in an environment of 130°C, 2.7atm, and 120%RH for 174 hours and its surface remained intact.

[0049] Example 2

[0050] This embodiment provides a method for preparing a permanent magnet surface coating material.

[0051] (1) Preparation of styrene-acrylic resin composite liquid:

[0052] Styrene acrylic resin, melamine formaldehyde resin, chromium oxide and methanol were weighed respectively according to a weight ratio of 1:0.3:0.05:0.7, and mixed and stirred evenly to form a styrene acrylic resin composite liquid.

[0053] (2) Preparation of zinc-based alloy powder:

[0054] Take the scrap of ZnAl27 alloy, put it into an induction furnace, add rare earth elements Sn, Pb, Y and Ce, melt them together at 750℃, and then cast them into alloy ingots;

[0055] The alloy ingot is placed in an induction furnace crucible for melting at a melting temperature of 720° C. After melting, the alloy ingot is kept warm for 5 minutes. The crucible is provided with a bottom hole with a diameter of 1 mm. After melting, the alloy ingot flows out from the bottom hole under the action of nitrogen pressure (1.1 atmospheres) and contacts the molybdenum alloy wheel rotating below the bottom hole of the crucible (the linear speed of the edge of the molybdenum alloy wheel is 20 m / s) to form an alloy strip; then the alloy strip is placed in a ball mill at -50° C. and crushed to form a zinc-based alloy powder with a particle size of 220 meshes;

[0056] The components and weight percentages of the prepared zinc-based alloy powder are as follows: Al is 25.0%, Mg is 0.01%, Cu is 2%, Sn is 0.25%, Pb is 0.04%, Y is 0.3%, Ce is 0.7%, and the rest is Zn.

[0057] (3) Preparation of ferrochromium alloy powder:

[0058] Take 304 stainless steel scrap, put it into an induction furnace, add rare earth elements Zr, Gd and Pd, melt them together at 1560℃, and then cast them into alloy ingots;

[0059] The alloy ingot is placed in an induction furnace crucible for melting at a melting temperature of 1580°C. After melting, the alloy is kept warm for 5 minutes. The crucible is provided with a bottom hole with a diameter of 1 mm. After the alloy is melted, it flows out from the bottom hole under the action of nitrogen pressure (1.1 atmospheres) and contacts the molybdenum alloy wheel rotating below the bottom hole of the crucible (the linear speed of the edge of the molybdenum alloy wheel is 20 m / s) to form an alloy strip; then the alloy strip is placed in a ball mill and crushed to form an iron-chromium alloy powder with a particle size of 220 meshes;

[0060] The components and weight percentages of the prepared ferrochromium alloy powder are as follows: 0.03% C, 1% Si, 2% Mn, 20% Cr, 8% Ni, 0.12% Zr, 0.1% Gd, 0.7% Pd, 0.04% P, 0.02% S, and the rest Fe.

[0061] (4) Preparation of permanent magnet surface coating material:

[0062] The zinc-based alloy powder and the iron-chromium alloy powder are uniformly mixed in a weight ratio of 1:0.5 to form an alloy composite powder;

[0063] The alloy composite powder, molybdenum dioxide powder and silicon carbide powder are mixed and stirred for 22 minutes at a stirring speed of 45 rpm, and then the styrene-acrylic resin composite liquid prepared in step (1) is slowly added, and the stirring is continued for 30 minutes at a stirring speed of 900 rpm to obtain a permanent magnet surface coating material. The weight percentage contents of the alloy composite powder, molybdenum dioxide powder and silicon carbide powder are 40%, 4% and 5% respectively, and the rest is the styrene-acrylic resin composite liquid.

[0064] (5) Application:

[0065] The permanent magnet surface coating material prepared in this embodiment is applied to the surface coating of a NdFeB magnet, and the corrosion resistance of the formed coating is tested.

[0066] After testing, the permanent magnet composite material was placed in an environment of 130°C, 2.7atm, and 120%RH for 180 hours and its surface remained intact.

[0067] Example 3

[0068] This embodiment provides a method for preparing a permanent magnet surface coating material.

[0069] (1) Preparation of styrene-acrylic resin composite liquid:

[0070] Styrene acrylic resin, melamine formaldehyde resin, chromium oxide and methanol were weighed respectively according to a weight ratio of 1:0.4:0.05:0.8, and mixed and stirred evenly to form a styrene acrylic resin composite liquid.

[0071] (2) Preparation of zinc-based alloy powder:

[0072] Take the scrap of ZnAl27 alloy, put it into an induction furnace, add rare earth elements Sn, Pb, Y and Ce, melt them together at 750℃, and then cast them into alloy ingots;

[0073] The alloy ingot is placed in an induction furnace crucible for melting at a melting temperature of 720° C. After melting, the alloy ingot is kept warm for 6 minutes. The crucible is provided with a bottom hole with a diameter of 1 mm. After melting, the alloy ingot flows out from the bottom hole under the action of nitrogen pressure (1.1 atmospheres) and contacts the molybdenum alloy wheel rotating below the bottom hole of the crucible (the linear speed of the edge of the molybdenum alloy wheel is 20 m / s) to form an alloy strip; then the alloy strip is placed in a ball mill at -40° C. and crushed to form a zinc-based alloy powder with a particle size of 220 meshes;

[0074] The components and weight percentages of the prepared zinc-based alloy powder are as follows: Al is 28.0%, Mg is 0.01%, Cu is 2%, Sn is 0.20%, Pb is 0.02%, Y is 0.1%, Ce is 0.6%, and the rest is Zn.

[0075] (3) Preparation of ferrochromium alloy powder:

[0076] Take 304 stainless steel scrap, put it into an induction furnace, add rare earth elements Zr, Gd and Pd, melt them together at 1500℃, and then cast them into alloy ingots;

[0077] The alloy ingot is placed in an induction furnace crucible for melting at a melting temperature of 1530° C. After melting, the alloy is kept warm for 5 minutes. The crucible is provided with a bottom hole with a diameter of 1 mm. After the alloy is melted, it flows out from the bottom hole under the action of nitrogen pressure (1.1 atmospheres) and contacts the molybdenum alloy wheel rotating below the bottom hole of the crucible (the linear speed of the edge of the molybdenum alloy wheel is 20 m / s) to form an alloy strip; then the alloy strip is placed in a ball mill and crushed to form an iron-chromium alloy powder with a particle size of 220 meshes;

[0078] The components and weight percentages of the prepared ferrochromium alloy powder are as follows: C is 0.06%, Si is 0.8%, Mn is 1.5%, Cr is 19%, Ni is 9%, Zr is 0.08%, Gd is 0.2%, Pd is 0.7%, P is 0.02%, S is 0.02%, and the rest is Fe.

[0079] (4) Preparation of permanent magnet surface coating material:

[0080] The zinc-based alloy powder and the iron-chromium alloy powder are uniformly mixed in a weight ratio of 1:0.7 to form an alloy composite powder;

[0081] The alloy composite powder, molybdenum dioxide powder and silicon carbide powder are mixed and stirred for 20 minutes at 40 revolutions per minute, and then the styrene-acrylic resin composite liquid prepared in step (1) is slowly added, and the stirring is continued for 30 minutes at 900 revolutions per minute to obtain a permanent magnet surface coating material. The weight percentages of the alloy composite powder, molybdenum dioxide powder and silicon carbide powder are 45%, 6% and 6% respectively, and the rest is the styrene-acrylic resin composite liquid.

[0082] (5) Application:

[0083] The permanent magnet surface coating material prepared in this embodiment is applied to the surface coating of a NdFeB magnet, and the corrosion resistance of the formed coating is tested.

[0084] After testing, the permanent magnet composite material was placed in an environment of 130°C, 2.7atm, and 120%RH for 178 hours and its surface remained intact.

[0085] Example 4

[0086] This embodiment provides a method for preparing a permanent magnet surface coating material.

[0087] (1) Preparation of styrene-acrylic resin composite liquid:

[0088] Styrene acrylic resin, melamine formaldehyde resin, chromium oxide and methanol were weighed respectively according to a weight ratio of 1:0.3:0.05:0.9, and mixed and stirred evenly to form a styrene acrylic resin composite liquid.

[0089] (2) Preparation of zinc-based alloy powder:

[0090] Take the scrap of ZnAl27 alloy, put it into an induction furnace, add rare earth elements Sn, Pb, Y and Ce, melt them together at 690℃, and then cast them into alloy ingots;

[0091] The alloy ingot is placed in an induction furnace crucible for melting at a melting temperature of 720° C. After melting, the alloy ingot is kept warm for 5 minutes. The crucible is provided with a bottom hole with a diameter of 1 mm. After melting, the alloy ingot flows out from the bottom hole under the action of nitrogen pressure (1.1 atmospheres) and contacts the molybdenum alloy wheel rotating below the bottom hole of the crucible (the linear speed of the edge of the molybdenum alloy wheel is 20 m / s) to form an alloy strip; then the alloy strip is placed in a ball mill at -40° C. and crushed to form a zinc-based alloy powder with a particle size of 220 meshes;

[0092] The components and weight percentages of the prepared zinc-based alloy powder are as follows: Al is 27%, Mg is 0.02%, Cu is 2%, Sn is 0.18%, Pb is 0.01%, Y is 0.3%, Ce is 0.6%, and the rest is Zn.

[0093] (3) Preparation of ferrochromium alloy powder:

[0094] Take 304 stainless steel scrap, put it into an induction furnace, add rare earth elements Zr, Gd and Pd, melt them together at 1500℃, and then cast them into alloy ingots;

[0095] The alloy ingot is placed in an induction furnace crucible for melting at a melting temperature of 1530° C. After melting, the alloy is kept warm for 5 minutes. The crucible is provided with a bottom hole with a diameter of 1 mm. After the alloy is melted, it flows out from the bottom hole under the action of nitrogen pressure (1.1 atmospheres) and contacts the molybdenum alloy wheel rotating below the bottom hole of the crucible (the linear speed of the edge of the molybdenum alloy wheel is 20 m / s) to form an alloy strip; then the alloy strip is placed in a ball mill and crushed to form an iron-chromium alloy powder with a particle size of 220 meshes;

[0096] The components and weight percentages of the prepared ferrochromium alloy powder are as follows: C is 0.07%, Si is 0.7%, Mn is 1.5%, Cr is 20%, Ni is 10%, Zr is 0.09%, Gd is 0.2%, Pd is 0.6%, P is 0.02%, S is 0.02%, and the rest is Fe.

[0097] (4) Preparation of permanent magnet surface coating material:

[0098] The zinc-based alloy powder and the iron-chromium alloy powder are uniformly mixed in a weight ratio of 1:0.5 to form an alloy composite powder;

[0099] The alloy composite powder, molybdenum dioxide powder and silicon carbide powder are mixed and stirred for 25 minutes at 40 revolutions per minute, and then the styrene-acrylic resin composite liquid prepared in step (1) is slowly added, and the stirring is continued for 20 minutes at 1000 revolutions per minute to obtain a permanent magnet surface coating material. The weight percentage contents of the alloy composite powder, molybdenum dioxide powder and silicon carbide powder are 33%, 2.6% and 2% respectively, and the rest is the styrene-acrylic resin composite liquid.

[0100] (5) Application:

[0101] The permanent magnet surface coating material prepared in this embodiment is applied to the surface coating of a NdFeB magnet, and the corrosion resistance of the formed coating is tested.

[0102] After testing, the permanent magnet composite material was placed in an environment of 130°C, 2.7atm, and 120%RH for 170 hours and its surface remained intact.

[0103] Example 5

[0104] This embodiment provides a method for preparing a permanent magnet surface coating material.

[0105] (1) Preparation of styrene-acrylic resin composite liquid:

[0106] Styrene acrylic resin, melamine formaldehyde resin, chromium oxide and methanol were weighed respectively according to a weight ratio of 1:0.2:0.05:0.7, and mixed and stirred evenly to form a styrene acrylic resin composite liquid.

[0107] (2) Preparation of zinc-based alloy powder:

[0108] Take the scrap of ZnAl27 alloy, put it into an induction furnace, add rare earth elements Sn, Pb, Y and Ce, melt them together at 700℃, and then cast them into alloy ingots;

[0109] The alloy ingot is placed in an induction furnace crucible for melting at a melting temperature of 720° C. After melting, the alloy ingot is kept warm for 5 minutes. The crucible is provided with a bottom hole with a diameter of 1 mm. After melting, the alloy ingot flows out from the bottom hole under the action of nitrogen pressure (1.1 atmospheres) and contacts the molybdenum alloy wheel rotating below the bottom hole of the crucible (the linear speed of the edge of the molybdenum alloy wheel is 20 m / s) to form an alloy strip; then the alloy strip is placed in a ball mill at -30° C. and crushed to form a zinc-based alloy powder with a particle size of 220 meshes;

[0110] The components and weight percentages of the prepared zinc-based alloy powder are as follows: Al is 25.0%, Mg is 0.02%, Cu is 2.5%, Sn is 0.25%, Pb is 0.01%, Y is 0.1%, Ce is 0.6%, and the rest is Zn.

[0111] (3) Preparation of ferrochromium alloy powder:

[0112] Take 304 stainless steel scrap, put it into an induction furnace, add rare earth elements Zr, Gd and Pd, melt them together at 1500℃, and then cast them into alloy ingots;

[0113] The alloy ingot is placed in an induction furnace crucible for melting at a melting temperature of 1580°C. After melting, the alloy is kept warm for 5 minutes. The crucible is provided with a bottom hole with a diameter of 1 mm. After the alloy is melted, it flows out from the bottom hole under the action of nitrogen pressure (1.1 atmospheres) and contacts the molybdenum alloy wheel rotating below the bottom hole of the crucible (the linear speed of the edge of the molybdenum alloy wheel is 20 m / s) to form an alloy strip; then the alloy strip is placed in a ball mill and crushed to form an iron-chromium alloy powder with a particle size of 220 meshes;

[0114] The components and weight percentages of the prepared ferrochromium alloy powder are as follows: 0.05% C, 1% Si, 2% Mn, 18% Cr, 8% Ni, 0.05% Zr, 0.3% Gd, 0.7% Pd, 0.05% P, 0.03% S, and the rest Fe.

[0115] (4) Preparation of permanent magnet surface coating material:

[0116] The zinc-based alloy powder and the iron-chromium alloy powder are uniformly mixed in a weight ratio of 1:0.5 to form an alloy composite powder;

[0117] The alloy composite powder, molybdenum dioxide powder and silicon carbide powder are mixed and stirred for 25 minutes at 40 revolutions per minute, and then the styrene-acrylic resin composite liquid prepared in step (1) is slowly added, and the stirring is continued for 20 minutes at 900 revolutions per minute to obtain a permanent magnet surface coating material. The weight percentages of the alloy composite powder, molybdenum dioxide powder and silicon carbide powder are 50%, 7% and 7% respectively, and the rest is the styrene-acrylic resin composite liquid.

[0118] (5) Application:

[0119] The permanent magnet surface coating material prepared in this embodiment is applied to the surface coating of a NdFeB magnet, and the corrosion resistance of the formed coating is tested.

[0120] After testing, the permanent magnet composite material was placed in an environment of 130°C, 2.7atm, and 120%RH for 172 hours and its surface remained intact.

[0121] From the above, it can be seen that the permanent magnet surface coating materials prepared in Examples 1 to 5 of the present invention maintain a surface integrity time (170 to 180 hours) under an environment of 130°C, 2.7atm, and 120%RH, which is higher than the surface integrity time (168 hours) of the prior art (CN 201810438127X). Therefore, the method of the present invention can significantly improve the corrosion resistance of the permanent magnet material.

[0122] The above are only preferred embodiments of the present invention, and the protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, some improvements and modifications without departing from the principle of the present invention should be regarded as the protection scope of the present invention.

Claims

1. A method for preparing a permanent magnet surface coating material, characterized in that: The following steps are involved: S1, mixing styrene-acrylic resin, melamine-formaldehyde resin, chromium oxide and methanol to form a styrene-acrylic resin composite liquid; the weight ratio of styrene-acrylic resin, melamine-formaldehyde resin, chromium oxide and methanol is 1:0.2~0.4:0.05:0.6~0.9; S2, mixing and stirring the alloy composite powder, molybdenum dioxide powder and silicon carbide powder, and then slowly adding the styrene acrylic resin composite liquid prepared in S1, stirring, to obtain a permanent magnet surface coating material, wherein the alloy composite powder is composed of zinc-based alloy powder and iron-chromium alloy powder; In S2, the composition and weight percentage of the zinc-based alloy powder are: Al is 25.0-28.0%, Mg is 0.01-0.02%, Cu is 2-2.5%, Sn is 0.15-0.25%, Pb is 0.01%-0.04%, Y is 0.1%-0.4%, Ce is 0.5%-0.7%, and the rest is Zn; the composition and weight percentage of the ferrochromium alloy powder are: C is 0.03-0.08%, Si is ≤1%, Mn is ≤2%, Cr is 18-20%, Ni is 8-11%, Zr is 0.05-0.12%, Gd is 0.1-0.4%, Pd is 0.5-0.7%, P is ≤0.05%, S is ≤0.03%, and the rest is Fe.

2. The method for preparing a permanent magnet surface coating material according to claim 1, characterized in that: In S2, the weight percentage contents of alloy composite powder, molybdenum dioxide powder and silicon carbide powder are 35-45%, 3-6% and 3-6% respectively, and the rest is styrene-acrylic resin composite liquid.

3. The method for preparing the permanent magnet surface coating material according to claim 1, characterized in that: In S2, in the alloy composite powder, the weight ratio of the zinc-based alloy powder to the iron-chromium alloy powder is 1:0.4~0.

7.

4. The method for preparing a permanent magnet surface coating material according to claim 1, characterized in that: In S2, the preparation method of the zinc-based alloy powder is: taking ZnAl27 alloy waste, putting it into an induction furnace, adding Sn, Pb, Y and Ce, melting them together, and then casting them into alloy ingots; putting the alloy ingots into an induction furnace crucible for melting, the crucible is provided with a bottom hole with a diameter of 1-2 mm, and the alloy flows out from the bottom hole under the action of nitrogen pressure after melting, and contacts with a molybdenum alloy wheel rotating below the bottom hole of the crucible to form alloy strips; then putting the alloy strips into a ball mill for crushing to form zinc-based alloy powder; Among them, the melting temperature of ZnAl27 alloy scrap, Sn, Pb, Y and Ce is 690~750℃; the melting temperature of alloy ingot is 720~750℃, and it is kept warm for 5~9min after melting; the nitrogen pressure is 1.1~1.3 atmospheres, and the linear speed of the edge of the molybdenum alloy wheel is 19~23m / s; the ball milling temperature is -30~-50℃, and the particle size of zinc-based alloy powder after ball milling is 220~250 mesh.

5. The method for preparing a permanent magnet surface coating material according to claim 1, characterized in that: In S2, the preparation method of the ferrochromium alloy powder is as follows: taking 304 stainless steel scrap, putting it into an induction furnace, adding Zr, Gd and Pd, melting them together, and then casting them into alloy ingots; putting the alloy ingots into an induction furnace crucible for melting, the crucible is provided with a bottom hole with a diameter of 1-2 mm, and after the alloy is melted, it flows out from the bottom hole under the action of nitrogen pressure and contacts with a molybdenum alloy wheel rotating below the bottom hole of the crucible to form alloy strips; then putting the alloy strips into a ball mill for crushing to form ferrochromium alloy powder; Among them, the temperature of melting 304 stainless steel scrap, Zr, Gd and Pd together is 1500~1560℃; the melting temperature of alloy ingot is 1530~1580℃, and it is kept warm for 5~10min after melting; the nitrogen pressure is 1.1~1.3 atmospheres, and the linear speed of the edge of the molybdenum alloy wheel is 18~24m / s; the particle size of the iron-chromium alloy powder after ball milling is 200~250 mesh.

6. The method for preparing a permanent magnet surface coating material according to claim 1, characterized in that: In S2, the alloy composite powder, molybdenum dioxide powder and silicon carbide powder are mixed and stirred for 20-25 minutes at a stirring speed of 40-50 rpm; after adding the styrene-acrylic resin composite liquid, the stirring time is 20-30 minutes at a stirring speed of 900-1000 rpm; The particle sizes of the alloy composite powder, molybdenum dioxide powder and silicon carbide powder are all 200-280 meshes.

7. The permanent magnet surface coating material prepared by the preparation method according to any one of claims 1 to 6.